The Role of Teachers and Students in Achieving Deep Learning with AI Integration at MAN 13 Jakarta - Korida, Imas; Jauzaa, Fardini Auralia; Pebri, Nisrina Nabila Putri; Hindun, Hindun (The Future of Education Journal, 2025)
This study examines the role of teachers and students in achieving deep learning based on Artificial Intelligence (AI) in the Indonesian Language subject at MAN 13 Jakarta, as a form of adaptation to the changing characteristics of Generation Z and the demands of 21st-century education. Using a descriptive qualitative approach with interview techniques, this research explores the application of the principles of mindful, meaningful, and joyful learning, as well as the stages of deep learning, including understanding, applying, and reflecting. The findings indicate that teachers act as facilitators who guide the wise use of AI through platforms such as Wordwall, Padlet, Canva, and Quizizz, while students play an active role as learners who utilize AI to obtain information, enrich literacy, and develop critical thinking skills. The principle of joyful learning emerges as the most dominant element in the teacher's learning practices, while meaningful learning is more prominent in the students' learning experiences. Although AI integration enhances interactivity and the relevance of learning, students' self-regulation skills in using AI still need further development. This study affirms that AI integration strengthens deep learning, but still requires teacher guidance to ensure that learning remains critical, creative, and responsible.